In relationship with a virus: An argument for new materialist thinking to be introduced into systemic thinking and an argument for why it has always already been there - Huhnen, Mark (Murmurations: Journal of Transformative Systemic Practice, 2021)
The current COVID-19 situation offers an opportunity for us to reconsider our relationship with the world and with our theories about this relationship. While systemic theory already offers many ways and ideas to consider this, in this article I offer another perspective, “new” materialism and highlight its fit with existing systemic theories.